Intercultural interactions in the multicultural workplace : traditional and positive organizational scholarship - Rozkwitalska, Malgorzata; Sulkowski, Lukasz, 1972-; Magala, Sławomir (Springer, 2016)
This volume explores the work environment in multinational corporations. To do so, it integrates studies on the organizational sciences, cross-cultural management, positive psychology and sociology within a single comprehensive framework. Twenty-two authors from six countries identify the challenges in multicultural workplaces, the positives of interactions, cultural clashes and their organizational preconditions. They add inter-organizational, institutional and critical perspectives to the analysis within the framework of multinationals and complex, hybrid cultural environments. The book addresses the needs of researchers in the areas of intercultural management, and those of practitioners in international human resource management.
Keywords: Industrial management.; Industrial organization.; Organizational behavior.; Ethnopsychology.; elektronické knihy; electronic books